Phylogenetic reappraisal of Rhytidosteidae (Stereospondyli: Trematosauria), temnospondyl amphibians from the Permian and Triassic - Dias Da Silva, Sérgio (2011)
All stereospondyl taxa previously placed within Rhytidosteidae are reviewed in a phylogenetic context. A parsimony analysis shows that Pneumatostega, Trucheosaurus, Rhytidosteus and Nanolania are placed outside Rhytidosteidae. If an implied weighting method is introduced in order to downweight homoplastic characters, then these taxa are placed within rhytidosteids (with the exception of Rhytidosteus), thus forming a resolved monophyletic group. This group is supported by four synapomorphies, including a twisted pterygoid quadrate ramus and sculpture consisting of a reticulate pattern with pustules or nodules at the junction between adjacent crests and ridges. Based on the topology of a majority rule consensus tree, we postulate a close relationship among all eastern Gondwanan rhytidosteids (Australian and Indian taxa) and among western Gondwanan taxa (South America, South Africa and Madagascar). Laurasian Boreopelta and Peltostega are successive paraphyletic taxa of both eastern and western groups. The Australian family 'Derwentiidae' is nested within Rhytidosteidae and is redefined as a subfamily (Derwentiinae nov.) which also includes Indobrachyops. Peltosteginae and Indobrachyopidae as currently defined in the literature are not supported. Rhytidosteinae is also not supported because Laidleria, Pneumatostega and Rhytidosteus do not emerge as a clade. The presence of the rhytidosteid Trucheosaurus major in the Late Permian of Australia suggests that rhytidosteids were already diversified at that time. Increasing efforts to collect Upper Permian and Lower Triassic rhytidosteids should help to improve stratigraphical, palaeogeographical and phylogenetic information regarding this widespread group of temnospondyls.